Quasi-relativistic center-of-mass variables in applications - Gaida, R.; Tretyak, V.; Yaremko, Yu. (Condensed Matter Physics, 1998)
Collective center-of-mass variables are introduced in the Lagrangian formalism
of the relativistic classical mechanics of directly interacting particles.
It is shown that the transition to the Hamiltonian formalism leads to
the Bakamjian-Thomas model. The quantum-mechanical system consisting
of two spinless particles is investigated. Quasi-relativistic corrections to
the discrete energy spectrum are calculated for some Coulomb-like interactions
having field theoretical analogues. У лаґранжевому формалізмі релятивістичної класичної механіки прямо взаємодіючих частинок введені колективні змінні центра мас. Показано, що відповідний гамільтонівформалізм веде до моделі Бакамджіяна–Томаса. Вивчається квантово-механічна система із двох безспінових частинок. Для низки кулоноподібних взаємодій, що мають теоретико-польові аналоги, підраховано квазірелятивістичні поправки до дискретного енерґетичного спектру.